HLA genetics in bipolar disorder. (4th June 2018) - Tamouza, R.; Oliveira, J.; Etain, B.; Bengoufa, D.; Hamdani, N.; Manier, C.; Mariaselvam, C.; Sundaresh, A.; Bellivier, F.; Henry, C.; Kahn, J‐P.; Krishnamoorthy, R.; et al.
Abstract : Objective: Bipolar Disorder (BD) is characterized by deregulated adaptive immune processes. Recent genome‐wide association studies (GWAS) implicate the major histocompatibility complex (MHC) region in BD. The present study investigates the potential influence of variations in human leukocyte antigen (HLA) on BD risk and/or clinical presentations. This may have relevance to the dysregulated inflammatory processes commonly found in BD. Method: DNAs from 475 BD patients and 195 healthy controls (HC) were genotyped for classical HLA class I and II loci. Results: We found that: (i) the HLA‐A*02 B*44 DRB1*07 sub‐haplotype is less prevalent in BD, vs. HC (pc = 2.4 × 10 −2 ); (ii) the 57.1 and the 8.1‐derived ancestral haplotypes i.e. HLA‐A*02 B*57 Cw*06 DRB1*07 DQB1*09 and HLA‐A*02 B*08 Cw*07 are associated with rapid cycling (pc = 1.9 × 10 −3 and 1.05 × 10 −2, respectively); (iii) the 8.1AH‐derived HLA class II‐DRB*03 HLA‐DQB1*02 sub‐haplotype is more frequent in BD patients with a history of suicidal behaviors (pc = 2.1 × 10 −2 ); and (iv) disease onset by an hypomanic episode or by psychotic symptoms are, respectively, more frequent in BD patients bearing the 7.1 AH‐derived A*03 B*07 DRB1*15 sub‐haplotype (pc = 8.5 × 10 −3 ) and the HLA‐A*02 B*07 DRB1*15 sub‐haplotype (pc = 4.0 × 10 −2 ). Conclusion: Corroborating the established link between these HLA haplotypes/sub haplotypes and common immune disorders, our findings suggest possible HLA‐mediated proinflammatory processes operating in BD.